Fabrication of TiO2/CdS/TiO2 Nanotube/Ti Mesh Electrode and Application in Photoelectro-catalytic Cell System for Degradation of Methylene Blue under Visible Light Illumination - Zeng, Qingyi; Li, Xinjun; Xi, Min; Wu, Liangpeng; Xu, Zhen; Zhou, Zhouyu (Asian Journal of Chemistry, 2013)
A TiO2/CdS/TiO2 nanotube/Ti mesh composite structure photoelectrocatalyst was fabricated by decorating the anodized TiO2 nanotubes (TNT) on Ti mesh with CdS nanoparticles via successive ionic layer adsorption and reaction and subsequently coated with a TiO2 protection layer via a vacuum dip-coating process. For the photoelectrocatalysts severed as the photoanodes, the transient photocurrent (iph) and linear sweep voltammetry (LSV) were investigated in a three-electrode system and the photoelectrocatalytic performance was evaluated in a photoelectrocatalytic cell (PEC) system for degradation of methylene blue under visible light illumination. The results show that the TiO2 nanotube arrays are decorated with relatively uniform CdS nanoparticles on the tube wall. Owing to the protection of TiO2 layer, the TiO2/CdS/TiO2 nanotube/Ti mesh electrode shows a stable and superior photoelectrocatalytic performance. The superimposition of mesh electrode can remarkably increase the photoelectrocatalytic efficiency for the degradation of methylene blue.